2002
DOI: 10.1053/jhep.2002.30317
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated increase in HNF-3β or HNF-3α shows differences in levels of liver glycogen and gene expression

Abstract: We previously generated a transgenic mouse line (T-77) in which increased hepatic expression of the hepatocyte nuclear factor-3␤ (HNF-3␤) protein was used to assess its role in hepatocyte-specific gene transcription. The T-77 transgenic mice displayed elevated serum bile acid and bilirubin levels and a complete absence of hepatic glycogen storage. These postnatal liver defects were associated with diminished expression of hepatocyte genes involved in gluconeogenesis and bile acid transport as well as reduced l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 44 publications
1
36
0
Order By: Relevance
“…The construction and preparation of the replication-defective AdHNF-6 or AdLacZ have been described previously. 11,15,16 Ribonuclease Protection Assay. Total RNA was prepared from whole mouse liver using RNA-STAT-60 (TelTest "B" Inc., Friendswood, TX).…”
Section: Methodsmentioning
confidence: 99%
“…The construction and preparation of the replication-defective AdHNF-6 or AdLacZ have been described previously. 11,15,16 Ribonuclease Protection Assay. Total RNA was prepared from whole mouse liver using RNA-STAT-60 (TelTest "B" Inc., Friendswood, TX).…”
Section: Methodsmentioning
confidence: 99%
“…Sund et al (16) have shown that Hnf1␣ and Hnf1␤ mRNA levels are unchanged, whereas Hnf4␣ mRNA expression is slightly elevated in the liver-specific Foxa2 knockout mice. Most recently, Tan et al (47) have demonstrated that adenovirus-mediated overexpression of Foxa2 in mouse liver led to drastic decrease in the mRNA levels of Hnf4␣ and Hnf1␣.…”
Section: Establishment Of a Cellular Model For Studying Foxa2 Functiomentioning
confidence: 99%
“…In addition, Sund et al (52) showed that HNF-1␣ and HNF-1␤ mRNA levels are unchanged, whereas HNF-4␣ mRNA is slightly elevated in mice with liver-specific deletion of Foxa2. Most recently, Tan et al (53) demonstrated that adenovirus-mediated overexpression of Foxa2 in mouse liver led to a drastic decrease in the expression of HNF-4␣ and HNF-1␣. The phenotype of mice with ␤-cell-specific deletion of Foxa2 is severe hyperinsulinemic hypoglycemia (54) rather than diabetes.…”
Section: Other Transcription Factors Implicated In ␤-Cell Functionmentioning
confidence: 99%